Design of human factor evaluations system using EEG and eye-tracking tools - Tan, Kia Meng (Nanyang Technological University, 2021)
Human Factors are essential in ensuring well-being and performance of operators in various systems and processes. In the age of digitalization and automation, integrating the needs of human operators into the operation of complex machines and systems can optimize their intended output and benefit society. Human Factors is a multi-disciplinary field encompassing many soft and hard sciences. Fatigue and Stress are common human factors and can be accurately detected by advancements in measurement tools like EEG and Eye-Tracking, and Machine Learning Algorithms. A Human Factors Evaluation System was proposed as a tool to assist Human Factors Researchers and Practitioners to make decisions on operators and procedures. It was designed to analyze and detect fatigue and stress from EEG/ET Data, as well as questionnaire data. Subsequently suggestions can be made to address the root cause and is supported by qualitative subject-dependent factors and task demands. It supports quick and easy processing and evaluation, with an alerts section and summary section for subjects and tasks, with functions such as Individual Performance Reports, Adaptive fatigue monitoring, dynamic redeployment. It might be easy to misuse and consider only the alerts. However, Human Factors is a very complex field and there is unlikely a clear and one-size-fits-all solution, or simple mathematical formula. This tool can assist but not replace final decision making. This system serves as a basis for future research, which could incorporate other human factors disciplines such as psychology, neuroscience, and other bio-signals such as heart rate.